Sustainable phosphorus management: reuse of recovered phosphorous in agriculture and impact of agricultural management practices on phosphorus speciation - Haputhanthri Gamage, Kasuni Hiranthika (Kansas State University, 2023)
The vital crop nutrient phosphorous (P) is essential in maintaining food security for a continuously growing world population. However, the mined rock phosphate, the primary P fertilizer source, will eventually become scarce as it is exploited at higher rates. Although applying nutrients to agricultural systems has resulted in a remarkable increase in yield, overloading nutrients to soil leads to environmental concerns, such as eutrophication and harmful algal blooms in surface waters. Therefore, the sustainable management of nutrients is a challenge, and exploring safe and efficient secondary P fertilizer sources is crucial. Wastewater is a renewable resource and recovered nutrient products (RNPs) from wastewater may contain high concentrations of plant-available nutrients such as P and are thus promising alternative fertilizers. The first three studies evaluated the effectiveness of contrasting groups of RNPs (Fe- and Ca-based) recovered from Fort Riley, Kansas municipal wastewater, synthetic, and real swine wastewater using an innovative anaerobic membrane bioreactor (AnMBR) technology. The objectives were to characterize the RNPs and compare the dissolution, transformations, and potential bioavailability of P in RNPs with conventional P fertilizers in selected calcareous, neutral, and acidic soils using short-term laboratory incubation studies. The RNPs were characterized using wet chemical methods, laboratory-based X-ray diffraction, scanning electron microscopy-energy dispersive X-ray, and X-ray absorption near edge structure (XANES) spectroscopy. The soil pH, total P (to assess diffusion), and resin extractable P (to assess potential plant availability) were measured in a spatially resolved manner with XANES spectroscopy in incubation study soil samples. While Fe was used for P recovery in municipal wastewater, the resulting RNP was rich in Fe-P, and as Ca was used for P recovery in synthetic and real swine wastewater, their resulting RNPs were rich in Ca-P. All tested RNPs showed less performance than the conventional fertilizers used. The Ca-based RNPs acted as a P source, and Fe-based RNP acted as a P sink for tested soils. Therefore, optimizing Ca-based RNP recovery will likely offer applicable secondary P sources for agriculture. The Fe-based RNP may be used as a P sink in specific agricultural systems where excessive P runoff threatens the ecosystem from land-applied P. Phosphorus loss from non-point agricultural sources is a crucial contributor to decreased surface water quality. Phosphorus can be found in both dissolved and sediment-bound forms in agricultural runoff. The dissolved P is mainly in the form of orthophosphate. Sediment-bound P is sorbed to the soil minerals and organic material in surface runoff. Although not readily available, sediment-bound P can contribute to continued eutrophication upon transformation to bioavailable P. Overall aims of the last study were to characterize and evaluate the effects of a five-year-long fertilizer (placement and source) and cover crop management on P speciation in surface runoff sediments and source soil collected from the Kansas Agricultural Watershed (KAW) field laboratory in Manhattan, Kansas. Runoff samples collected throughout 2020 and the source soil collected in 2019 fall were analyzed using a modified sequential extraction scheme for indirect P speciation. Direct P speciation was done using XANES spectroscopy. The P fractionation results showed that P and cover crop management affected the exchangeable, organic-associated, and iron-bound P fractions in sediments and exchangeable and residual fractions in source soil. The XANES analysis showed a depletion of iron-associated P in soil and sediment from cover crop systems, suggesting that changes in iron-associated P play a vital role in the solubility of P in different management systems. This study contributes to the mechanistic understanding needed in developing P fertilizer and cropping system management options that improve agricultural and environmental sustainability.
Keywords: Phosphorus; Recovered nutrient products; Wastewater; Cover crops; Runoff sediments; Soil